Commercialization of Health Care 2005
DOI: 10.1057/9780230523616_3
|View full text |Cite
|
Sign up to set email alerts
|

Multinational Corporations and Health Care in the United States and Latin America: Strategies, Actions and Effects

Abstract: In this article we analyze the corporate dominance of health care in the United States and the dynamics that have motivated the international expansion of multinational health care corporations, especially to Latin America. We identify the strategies, actions, and effects of multinational corporations in health care delivery and public health policies. Our methods have included systematic bibliographical research and in-depth interviews in the United States, Mexico, and Brazil. Influenced by public policy make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
0
23
0
2
Order By: Relevance
“…The vast majority of the literature has focused on specific case studies, rather than accounting for the actual magnitude of internationalisation taking place through this mode of supply. In these studies, the United States has been regarded as an important source country for health care service firms establishing abroad, in particular in Latin America and the United Kingdom (Holden 2002;Jasso-Aguilar, Waitzkin et al 2004). One particular study of the United Kingdom found that 22% of all independent hospital beds were owned by the United States (Mohan 1991: 857 cited in Holden 2002).…”
Section: What Is It?mentioning
confidence: 99%
“…The vast majority of the literature has focused on specific case studies, rather than accounting for the actual magnitude of internationalisation taking place through this mode of supply. In these studies, the United States has been regarded as an important source country for health care service firms establishing abroad, in particular in Latin America and the United Kingdom (Holden 2002;Jasso-Aguilar, Waitzkin et al 2004). One particular study of the United Kingdom found that 22% of all independent hospital beds were owned by the United States (Mohan 1991: 857 cited in Holden 2002).…”
Section: What Is It?mentioning
confidence: 99%
“…As shown in Table 1, foreign-operated hospitals are established in Western Europe and Australia. Hospital corporations own the for-profit hospitals that they operate [14]. In smallspecialized clinics, i.e.…”
Section: Fdi In the Health Care Sectormentioning
confidence: 99%
“…The Human Capital Index used in this study is a weighted average of the literacy rate and enrolment ratios (secondary school and tertiary education). 14 Data are available for 41 countries for which at least two MNCs have an office (branch and/or affiliate). The most popular location is Hong Kong (China), followed by Singapore, Mexico, and China in that order.…”
Section: Data and Empirical Analysismentioning
confidence: 99%
“…3 Mais recentemente, alguns autores admitem a Venezuela, com o programa denominado Misión Barrio Adentro, como a única alternativa, junto a Cuba, contra a tendência neoliberal de reformas setoriais que teriam afetado todos os países da América Latina (MUNTANER et al, 2006). Essa opinião parece ignorar a experiência brasileira, pois apesar das tentativas de influência dos organismos internacionais, particularmente o Banco Mundial, para realizar reformas setoriais orientadas para o mercado (JASSO-AGUILAR et al, 2004), o Brasil formulou o seu projeto de Reforma Sanitária na década de 80 com um sentido completamente diverso. A reforma não decorreu de uma iniciativa das áreas econômicas do Poder Executivo nem de uma indução internacional, como no caso da Colômbia, nem de um processo revolucionário como Cuba (DE VOS et al, 2006), mas desenvolveu-se numa conjuntura de transição democrática, com ampla participação da sociedade civil.…”
unclassified